San Andreas fault earthquake hazard model validation using probabilistic analysis of precariously balanced rocks and Bayesian updating - Rood,AH; Stafford,PJ; Rood,DH (Seismological Research Letters, 2024)
The Mojave section of the San Andreas fault is the closest section to the megacity of greater Los Angeles. A major issue for the population is that the lifethreatening hazard estimate of a future rare, large earthquake on this fault section is highly uncertain and untested at timescales and ground motions beyond limited historical recordings. Of relevance to this issue is that the nearby precariously balanced rocks at Lovejoy Buttes have survived these ground motions, despite the past tens of thousands of years of San Andreas fault earthquakes. Therefore, the fragility and age of these precariously balanced rocks provide crucial groundmotion constraints over the timescales of rare, large San Andreas fault earthquakes. We rigorously validate and update an earthquake hazard model for the Mojave section of the San Andreas fault using the independent observational data of precariously balanced rock survival at Lovejoy Buttes. The joint probability of survival of all five studied precariously balanced rocks was used to validate the hazard estimates and reweight the estimates using new Bayesian updating methods to deliver an improved, precariously balanced rockinformed earthquake hazard estimate. At an annual frequency of exceedance of 1 x 10^-4 yr^-1, equivalent to a mean return period of 10,000 yr, the precariously balanced rock survival data significantly reduced the mean hazard groundmotion estimate by 65% and the 5th–95th fractile uncertainty range by 72%. The magnitude of this inconsistency provides striking evidence for the need to reevaluate both the source and groundmotion components of our earthquake hazard model for the southern San Andreas fault.